Upaya Meningkatkan Prestasi Belajar Pendidikan Agama Islam dengan Menerapkan Model Pembelajaran PAKEM pada Siswa Kelas Vll SMPN 17 Kota Tangerang Selatan - Emi Jamiah (Jurnal Manajemen & Pendidikan [JUMANDIK], 2024)
The success of the teaching and learning process in the classroom is largely determined by the learning strategy, however complete and clear the other components, without being implemented through the right strategy, these components will have no meaning in the process of achieving goals. Therefore, every teacher will teach is required to apply certain strategies or methods in the implementation of learning. This study aims to determine the effect of student motivation after applying the PAKEM learning model. This study used three rounds of action research. Each round consists of four stages: design, activity and observation, reflection, and reference. The target of this study is grade VII students. The results of the analysis found that student learning achievement increased from cycle I to cycle III, namely, cycle I (68.00%), cycle II (80.00%), cycle III (92.00%). This means that the PAKEM learning model can have a positive effect on the learning motivation of VII students and this learning model can be used as an alternative to PAI learning.